A scalable framework for healthcare monitoring application using the Internet of Medical Things. (14th June 2020) - Balasubramanian, Venki; Jolfaei, Alireza
Summary: Internet of Things (IoT) is finding application in many areas, particularly in health care where an IoT can be effectively used in the form of an Internet of Medical Things (IoMT) to monitor the patients remotely. The quality of life of the patients and health care outcomes can be improved with the deployment of an IoMT because health care professionals can monitor conditions; access the electronic medical records and communicates with each other. This remote monitoring and consultations might reduce the traditional stressful and costly exercise of frequent hospitalization. Also, the rising costs of health care in many developed countries have influenced the introduction of the Healthcare Monitoring Application (HMA) to their existing health care practices. To materialize the HMA concepts for successful deployment for civilian and commercial use with ease, application developers can benefit from a generic, scalable framework that provides significant components for building an HMA. In this chapter, a generic maintainable HMA is advanced by amalgamating the advantages of event‐driven and the layered architecture. The proposed framework is used to establish an HMA with an end‐to‐end Assistive Care Loop Framework (ACLF) to provide a real‐time alarm and assistance to monitor pregnant women.